Construct specification equations: 'Recipes' for certified reference materials in cognitive measurement. (December 2021) - Melin, J.; Cano, S.J.; Flöel, A.; Göschel, L.; Pendrill, L.R.
Abstract: Construct specification equations (CSEs), providing a comprehensive understanding of the construct purported to be measured and how a collection of items works together causally, are candidate 'recipes for certified reference materials' (CRM). Analogous to the role of CRMs in areas such as chemistry and material properties, CSEs appear to provide metrological traceability in the human sciences. In this work we illustrate how memory test items, Rasch Measurement Theory (RMT) and CSEs can be brought together to help 'tell a clearer story' about memory decline that links language- and cultural-free items (blocks, digits) to more complex word recall. Combining different test items to form novel cognitive metrics, done carefully so not jeopardize validity and to enhance coherence in item design and purpose, is guided by entropy-based equivalence criteria identified in the CSEs. The novel NeuroMET Memory Metric may enable better-informed high stakes decision-making and more efficient and valid cognitive assessment.